Enfoque para el análisis de la crisis económica global y la salud (2009)
ABSTRACT: It begins by recognizing several areas for analysis of the global crisis in relation to health. It then focuses on the analysis of some aspects of the economic crisis, policy alternatives to mitigate the financial crisis and the identification of health indicators more sensitive to the vagaries of the economy. Objective: To propose some basis for analyzing the financial crisis of 2008 and its effects on health in the world. Methodology: it based on the analysis of the possible effects of the economic crisis on health after consider four essential axes: the conditions of life and health determinants, indicators of socio-demographic and epidemiological changes, the total public expenditure and spending on health and monitoring of policies to mitigate the crisis. Conclusion: The first crisis of globalization of the present century will have serious health implications and should lead to rethinking the global economic system based on State control and regulation of the markets. To avoid adverse effects on the environment and health, it is proposed addressing the determinants of global influences, to stimulate public policies that invest in health, boost action in international health legislation, and finally, to establish and implement a crisis system monitoring and its effect on health.